Steve Earle with special guest Allison Moorer : November 2008. - Frontier Touring ([Albert Park, VIc.] : Frontier Touring Co., 2008)
Poster advertising 2008 Australian tour by Steve Earle, supported by Allison Moorer. Features a black, white, and gold illustration of a dog covered in flowers. The dog is facing away from the viewer, and has a docked tail. Tour dates and venues listed at foot.
Caption title.
At head of caption title: The Frontier Touring Co. present.
Keywords: Earle, Steve; Moorer, Allison; Alternative country music -- Australia -- Posters; Country music -- Australia -- Posters; Concerts -- Australia -- Posters; Popular music -- Australia -- Posters; Posters, Australian; Australia -- Posters; Australian